Correlation between Pregnant Women’s Anxiety Level and Their Decision toward COVID-19 Vaccine Acceptance - Kyrie Hanna; Mutiara Indah Sari; Hidayat Hidayat; M. Aron Pase (Sumatera Medical Journal, 2023)
Introduction: High number of COVID-19 cases cause various effects, namely increased anxiety and depression in pregnant women, who are susceptible to transmission. To prevent further transmission, a vaccination policy was implemented which then elicited various responses. Low percentage of pregnant women’s willingness to be vaccinated was found. This happened because of anxiety and hesitancy towards COVID-19 vaccine among them. Objective: Knowing the correlation between the level of anxiety in pregnant women towards COVID-19 vaccine and the decision to accept COVID-19 vaccine at Abadijaya Public Health Center, Depok. Methods: Analytic with cross sectional method is used. Population and sample of this study were 96 pregnant women who visited Abadijaya Public Health Center, Depok. Results: Analysis conducted using chi squared and fisher’s exact test shows majority of pregnant women do not experience symptoms of anxiety (50%), no correlation between age, gestational age, gravidity, occupation and education level on the decision to accept COVID-19 vaccine, and correlation between pregnant women’s anxiety levels and the decision to accept COVID-19 vaccine was found (p value = 0.000). Conclusion: There is a correlation between anxiety levels in pregnant women towards COVID-19 vaccine and the decision to accept COVID-19 vaccine at Abadijaya Public Health Center, Depok.